Kinesiophobia as a Barrier to Symptom Management Using Physical Activity When undergoing Cancer Therapy: A Preparatory Study Describing Patients’ Experiences With the New Instrument Tampa-Scale for Kinesiophobia-Symptoms and Interviews - Tove Bylund-Grenklo MSc Psychology, PhD; Anna Efverman BSP, PhD (Integrative Cancer Therapies)
Background: Cancer care professionals need to be aware of kinesiophobia, fear of motion, in patients undergoing cancer therapy. The new instrument the Tampa-Scale Kinesiophobia Symptoms (TSK-Symptoms) aims to measure fear and avoidance of motion in relation to multiple symptoms (eg, nausea, fatigue, anxiety, pain). It is modified from the TSK, which relates solely to pain. Aim: To test the feasibility of the TSK-Symptoms, to quantify kinesiophobia in patients with cancer, to study whether kinesiophobia was associated with symptoms or physical activity, and through interviews to gain a deeper understanding of patient experiences. Methods: In this preparatory longitudinal study, patients (n = 55, mean age 68 years; 51% men; 38% had prostate cancer, 23% breast cancer) undergoing radiotherapy provided questionnaire data on kinesiophobia using the new instrument TSK-Symptoms, symptoms and physical activity twice (at baseline, T1, and 1 week later, T2). Eight patients were interviewed. Results: At T1 and T2, 4 of 54 (7%) and 8 of 55 patients (14%) reported kinesiophobia ( P  = .009). From T1 to T2, occurrence of nausea increased. Of the 16 nauseated patients at T2, 6 (38%) reported kinesiophobia compared to 2 (5%) of the 39 nausea-free patients ( P  = .005). Patients who reported kinesiophobia practiced less physical activity (median 0 days at moderate intensity at T1 ( P  < .001), median 2 days at moderate intensity at T2, P  = .006) compared to patients free from kinesiophobia (median 4 and 5 days). Three qualitative content analysis categories described patient experiences: (1) “Struggling to stay physically active in an extraordinary situation associated with burdensome symptoms,” (2) “Feeling damaged and at the same time grateful,” and (3) “Needing support due to fear of motion and of worsened condition.” Conclusions: This preparatory study showed that the new instrument the TSK-Symptoms was feasible for use in patients undergoing cancer therapy to quantify kinesiophobia, which was present in approximately 1 in 10 patients. Kinesiophobia was more common in patients with nausea, and patients reporting kinesiophobia practiced less physical activity. Patients highlighted a need for support. The psychometric properties of the TSK-Symptoms, completed on several languages, need to be evaluated. Cancer care professionals may quantify kinesiophobia using the TSK-Symptoms instrument and give kinesiophobic patients support.